Frequency and Genetic Determinants of Tigecycline Resistance in Clinically Isolated Stenotrophomonas maltophilia in Beijing, China - Zhao, Jin; Liu, Yunxi; Liu, Yi; Wang, Dong; Ni, Wentao; Wang, Rui; Liu, Youning; Zhang, Bo (Frontiers in Microbiology, 2018)
Stenotrophomonas maltophilia is an emerging nosocomial pathogen with high resistance to most clinically used antimicrobials. Tigecycline is a potential alternative antimicrobial for S. maltophilia infection treatment, but its resistance mechanism in clinical isolates is not fully elucidated. We investigated the antimicrobial susceptibility of 450 S. maltophilia isolated during 2012–2015 from three university hospitals in Beijing, China. These strains exhibited high susceptibility to minocycline (98.44%), sulfamethoxazole/trimethoprim (87.56%), tigecycline (77.78 %), doxycycline (81.33%), levofloxacin (67.56%) and ticarcillin/clavulanate (73.00%). The susceptibility of tigecycline-nonsusceptible strains (TNS) to doxycycline and levofloxacin was much lower than that of tigecycline-susceptible strains (TSS) (25.00% vs. 97.71% for doxycycline, P < 0.001; 17.00% vs. 82.00% for levofloxacin, P < 0.001). We further selected 48 TNS and TSS and compared the detection rate of eight tetracycline-specific genes by PCR and the expression level of six intrinsic multidrug resistance efflux pumps by real-time PCR. Only one tetB and two tetH genes in TNS and three tetH genes in TSS were detected, and the detection rate had no difference. The average expression level of smeD in TNS was higher than that in TSS [20.59 (11.53, 112.54) vs. 2.07 (0.80, 4.96), P < 0.001], while the average expression levels of smeA, smeI, smeO, smeV, and smrA were not significantly different, indicating that smeDEF was the predominant resistance genetic determinant in clinical S. maltophilia. Higher smeD expression was also observed in levofloxacin- and doxycycline-nonsusceptible isolates than in their corresponding susceptible isolates [16.46 (5.83, 102.24) vs. 2.72 (0.80, 6.25) for doxycycline, P < 0.001; 19.69 (8.07, 115.10) vs. 3.01(1.00, 6.03), P < 0.001], indicating that smeDEF was also the resistance genetic determinant to levofloxacin and doxycycline. The consistent resistance profile and common resistance genetic determinant highlight the importance of rational use of tigecycline for preventing the occurrence and spread of multidrug resistance.